Pengaruh model anyaman serat kulit pohon waru (Hibiscus Tiliceus) terhadap kekuatan tarik komposit - Arief Rizki Fadhillah; Nova Risdiyanto Ismail; Dadang Hermawan; Renada Julia Sakinah (TURBO [Tulisan Riset Berbasis Online], 2022)
Waru tree bark fiber (hibiscus tiliceus) has potential as a natural fiber composite reinforcement, but further research is needed by focusing on the woven fiber model on the strength of the waru tree bark composite material. The problem to be studied is "The Effect of the Model of Waru (hibiscus tiliceus) Bark Fiber Weaving on the Tensile Strength of Composites". The specific objective of this study was to analyze the effect of the woven model of hibiscus tree bark (hibiscus tiliceus) on the tensile strength of the composite in terms of ultimate strength, strain, and modulus of elasticity. The urgency of this research is that the composite of hibiscus bark fiber without woven has a tensile load concentration that is very difficult to predict, so it is necessary to have a model of woven hibiscus bark fiber. The method used in this study is an experimental method. The composite molding process uses the vaccum infusion resin method with a variety of woven models, including: Plain 1-1, Twill 2-1, Satin 3-1, Basket 2-2. The matrix used is Bisphenol A LP-1Q resin and the reinforcement used is hibiscus tiliaceus bark fiber. The analysis carried out in this study, among others: Analysis of composite tensile strength and composite fracture analysis. The type of woven fiber affects the tensile strength of the composite. Therefore, it can be recommended that waru tree bark fiber is more suitable when using basket woven model fiber (2-2) than using unidirectional fiber model.